Metabolic Impact on the Hypothalamic Kisspeptin-Kiss1r Signaling Pathway - Wahab, Fazal; Atika, Bibi; Ullah, Farhad; Shahab, Muhammad; Behr, Rüdiger (Frontiers in Endocrinology, 2018)
A large body of data has established the hypothalamic kisspeptin and its receptor, KISS1R, as major players in the activation of the neuroendocrine reproductive axis at the time of puberty and maintenance of reproductive capacity in the adult. Due to its strategic location, this ligand-receptor pair acts as an integrator of cues from gonadal steroids as well as of circadian and seasonal variation-related information on the reproductive axis. Besides these cues, the activity of the hypothalamic kisspeptin signaling is very sensitive to the current metabolic status of the body. In conditions of energy imbalance, either positive or negative, a number of alterations in the hypothalamic kisspeptin signaling pathway have been documented in different mammalian models including nonhuman primates and human. Deficiency of metabolic fuels during fasting causes a marked reduction of Kiss1 gene transcript levels in the hypothalamus, and hence decreases the output of kisspeptin containing neurons. Food intake or exogenous supply of metabolic cues such as leptin, reverse metabolic insufficiency-related changes in the hypothalamic kisspeptin signaling. Likewise, alterations in Kiss1 expression have also been reported in other situations of energy imbalance like diabetes and obesity. Information related to the body’s current metabolic status reaches to kisspeptin neurons both directly as well as indirectly via a complex network of other neurons. In this review article, we have provided an updated summary of the available literature on the regulation of the hypothalamic kisspeptin-Kiss1r signaling by metabolic cues. In particular, the potential mechanisms of metabolic impact on the hypothalamic kisspeptin-Kiss1r signaling, in light of available evidence, are discussed.